2023
DOI: 10.1021/acs.jctc.3c00899
|View full text |Cite
|
Sign up to set email alerts
|

Is the Functional Response of a Receptor Determined by the Thermodynamics of Ligand Binding?

Martin Vögele,
Bin W. Zhang,
Jonas Kaindl
et al.

Abstract: For an effective drug, strong binding to the target protein is a prerequisite, but it is not enough. To produce a particular functional response, drugs need to either block the proteins' functions or modulate their activities by changing their conformational equilibrium. The binding free energy of a compound to its target is routinely calculated, but the timescales for the protein conformational changes are prohibitively long to be efficiently modeled via physics-based simulations. Thermodynamic principles sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…This corroborated the preliminarily determined Kd value of ~15 µM in MST. A recent computational study using the binding free-energy perturbation method reported unprecedented performance in classifying ligands as agonists or antagonists for various receptors, including GPCRs [37]. The estimated affinity of CDR2-NDP P4 was similar to a previously characterized Nb71 CDR3-NDP P3; therefore, the β 2 AR:P3 complex exhibited a −∆G of 7.23 ± 0.04 kcal/mol or a Ki of 7.9 ± 0.5 µM [17].…”
Section: Discussionmentioning
confidence: 78%
“…This corroborated the preliminarily determined Kd value of ~15 µM in MST. A recent computational study using the binding free-energy perturbation method reported unprecedented performance in classifying ligands as agonists or antagonists for various receptors, including GPCRs [37]. The estimated affinity of CDR2-NDP P4 was similar to a previously characterized Nb71 CDR3-NDP P3; therefore, the β 2 AR:P3 complex exhibited a −∆G of 7.23 ± 0.04 kcal/mol or a Ki of 7.9 ± 0.5 µM [17].…”
Section: Discussionmentioning
confidence: 78%
“…The calculated shift in binding affinity was used to successfully classify the compounds as agonists, partial agonists, or antagonists. In another study, a team from the computational chemistry software company Schrödinger performed absolute binding free energy calculations of ligands to active and inactive conformations of 7TMR and nuclear hormone receptor targets 5 . Based on higher predicted binding affinity to the active conformation, 168 of 180 ligands (93%) could be correctly classified as agonists opposed to antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…Our study provides the first evidence for what could be a scientific law. While recent work has categorized ligands as active or inactive (or partially active) based on binding affinities to two conformations 4,5 , our approach accurately computes signaling efficacy along multiple pathways.…”
mentioning
confidence: 99%
“…Last year, Wang et. al presented a technique for categorizing ligands as agonists or antagonists using the absolute binding free energy perturbation method based on thermodynamic principles, which has been validated on multiple GPCRs . Recently, Milka et.…”
Section: Discussionmentioning
confidence: 99%
“…al presented a technique for categorizing ligands as agonists or antagonists using the absolute binding free energy perturbation method based on thermodynamic principles, which has been validated on multiple GPCRs. 59 Recently, Milka et. al used protein− peptide docking, molecular dynamic simulations, and metadynamic-based free-energy binding calculations to analyze the specific binding of complementary determinant regions of nanobody to the agonist-activated β2 adrenergic receptor.…”
Section: ■ Conclusionmentioning
confidence: 99%